Physical inactivity, and its association with hypertension among employees in the district of Colombo - A. U. Gamage; R. de A. Seneviratne (BMC, 2021)
Abstract Background Physical inactivity is a leading cause of morbidity and mortality and is a major public health problem. Insufficient activity is responsible for a large proportion of non-communicable diseases such as hypertension. Objectives The purpose of this study was to assess socioeconomic variations in physical activity and to measure the association between physical inactivity and hypertension among government officials in Sri Lanka. Methods A cross-sectional study was carried out among 275 senior-officers(SOs) and 760 managerial-assistants(MAs) aged 30-60 years and attached to Public Administration institutions in Colombo District in Sri Lanka. Physical-activity(PA) was gathered using the International Physical Activity Questionnaire(IPAQ) adopted and validated to the Sri Lankan context. Blood pressure(measured and classified using JNC-7 guidelines) and anthropometric indices were recorded. Energy utilization of all vigorous and moderated PA and walking was expressed as metabolic-equivalent-of-task(MET) min per week. A total-MET-score was calculated and categorized based on IPAQ guidelines. Results Socioeconomic variations in PA levels were observed as 58.1%(n = 158) SOs and 30.6%(n = 226) MAs were involved in inadequate PA. Among the SOs diagnosed with hypertension, more half(59.1%; n = 52) were physically inactive, while among MAs, 65.9%(n = 143) with hypertension were physically inactive. After adjusting for potential confounding factors being physically inactive was associated with a higher risk of hypertension among SOs[OR 2.08 [95% CI 1.07, 4.6] and MAs[OR 2.8 [95% CI 1.8, 4.6]. The main modality of commuting to work for SOs(59%) was private transport, and MAs(64%) public transport Commuting distance was positively correlated(p < 0.05) with total transport MET among SOs and MAs. After adjusting for confounders, commuting distance of > 20 km was found to lower the odds of hypertension among SOs and MAs(OR = 0.713; 95% CI 0.4 to1.3; and OR = 0.63; 95% CI 0.46 to 0.87). Conclusion Despite the current knowledge that being physically active promotes health, the practice was different. Physical inactivity was associated with hypertension and prevalent among both SOs and MAs. Higher commuting distance is positively correlated with total transport MET and associated with lower odds of hypertension among SOs and MAs. Longitudinal studies are required to provide a causative association between physical inactivity and hypertension among these employees.